Spaceflight and ageing: reflecting on Caenorhabditis elegans in space - Honda, Y.; Honda, S.; Narici, M.; Szewczyk, N.J. (Karger, 2014)
The prospect of space travel continues to capture the imagination. Several competing companies are now promising flights for the general population. Previously, it was recognized that many of the physiological changes that occur with spaceflight are similar to those seen with normal ageing. This led to the notion that spaceflight can be used as a model of accelerated ageing and raised concerns about the safety of individuals engaging in space travel. Paradoxically, however, space travel has been recently shown to be beneficial to some aspects of muscle health in the tiny worm Caenorhabditis elegans. C. elegans is a commonly used laboratory animal for studying ageing. C. elegans displays age-related decline of some biological processes observed in ageing humans, and about 35% of C. elegans' genes have human homologs. Space flown worms were found to have decreased expression of a number of genes that increase lifespan when expressed at lower levels. These changes were accompanied by decreased accumulation of toxic protein aggregates in ageing worms' muscles. Thus, in addition to spaceflight producing physiological changes that are similar to accelerated ageing, it also appears to produce some changes similar to delayed ageing. Here, we put forward the hypothesis that in addition to the previously well-appreciated mechanotransduction changes, neural and endocrine signals are altered in response to spaceflight and that these may have both negative (e.g. less muscle protein) and some positive consequences (e.g. healthier muscles), at least for invertebrates, with respect to health in space. Given that changes in circulating hormones are well documented with age and in astronauts, our view is that further research into the relationship between metabolic control, ageing, and adaptation to the environment should be productive in advancing our understanding of the physiology of both spaceflight and ageing.